1995
DOI: 10.21273/horttech.5.3.274
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' Preference for Insecticide-free Pumpkins in Eastern Kansas

Abstract: A survey conducted at farmers' markets in eastern Kansas showed that more consumers purchased pumpkins for jack-o-lanterns than for cooking. One to four jack-o-lantern pumpkins are purchased annually per consumer. Whether or not the pumpkins are treated with insecticides to control squash bugs and regardless of their intended use, consumers preferred U.S. no. 1 grade, which sell at the higher retail price of $0.33/kg. At least 90% of the consumers surveyed would pay 20% more than the retail price for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Respondents in our study reported that the most important factor was that the flowering plant has no plant damage. Similarly, multiple surveys demonstrate that consumers may be willing to pay a premium for organically grown but still expect a similar quality to the conventionally managed crops (Jetter and Paine, 2004;Ott, 1990;Olson et al, 1995;Thompson and Kidwell, 1998;Wells et al, 1994). The second most important factor in our study was that the ''plants have no insects on them'' whereas the third most important factor was that the ''flowering plants have no pesticide residue on or in the plant leaves.''…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Respondents in our study reported that the most important factor was that the flowering plant has no plant damage. Similarly, multiple surveys demonstrate that consumers may be willing to pay a premium for organically grown but still expect a similar quality to the conventionally managed crops (Jetter and Paine, 2004;Ott, 1990;Olson et al, 1995;Thompson and Kidwell, 1998;Wells et al, 1994). The second most important factor in our study was that the ''plants have no insects on them'' whereas the third most important factor was that the ''flowering plants have no pesticide residue on or in the plant leaves.''…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, participants reported that they would only be willing to spend $23 for chemical management of the eucalyptus snout beetle (Jetter and Paine, 2004). Similarly, most consumers surveyed (90%) in another study indicated they would pay 20% more for a pesticide-free pumpkin (Olson et al, 1995). While research has suggested that some consumers value reduced pesticide usage, the National Gardening Association (NGA) reported that 24% of all U.S. households (29 million) controlled insects on plants in 2012, an increase of 1 million households compared with the 5-year average (28 million) (Butterfield and Baldwin, 2013).…”
mentioning
confidence: 99%
“…mation is available on management of pumpkin diseases in the southeastern coastal plain. Minimizing pesticide inputs may improve the profit margin of the crop (Olson et al, 1995), although some fungicide must be applied to prevent premature defoliation and senescence.…”
Section: Methodsmentioning
confidence: 99%
“…Human issues in horticulture research conducted by horticulture faculty regarding horticulture products has been on widely varied topics. Examples include: the use of focus groups to determine product market potential (Barton et al, 1996), surveys of consumer preferences regarding pesticide free pumpkins (Olson et al, 1995), and florists' actions regarding the recruitment of commercial accounts (Anderson et al, 1996).…”
Section: Research On Human Issues In Hor-ticultural Industriesmentioning
confidence: 99%